Sintering and Characterization of Rare Earth Doped Bismuth Titanate Ceramics Prepared by Soft Combustion Synthesis - Al-Amani, Umar (InTech, 2012)
Nowadays, ferroelectric ceramics and thin films have attracted much attention for various studies which are generally used for numerous potential applications in ferroelectric random access memory (FRAM), in microelectronic mechanical system (MEMS), non-linear optical devices, surface acoustic wave devices, tunable capacitors, sensing applications or pyroelectric detectors (Besland et al., 2006, Yang et al., 2008). The main focus to develop the ferroelectric thin films has started in 1980s (Besland et al., 2006). Several methods were initially used for deposition of thin films such as conventional dipping, sputtering and spin coating techniques. Typically, the deposition of thin films will be more complex to obtain a good layer that consists of several ferroelectric compounds on substrate. Furthermore, high precision deposition technique is essential to control the desired thickness and surface layer of ferroelectric compounds. As far as our concern, the up to date technique such as physical vapor deposition (PVD), RF sputtering, chemical vapor deposition (CVD) and metal-organic chemical vapor deposition have been frequently used in many studies to obtain a better ferroelectric thin films condition. Nevertheless, a major concern on expensive equipment and experience user limit this technique in many studies. In order to develop the ferroelectric materials, the preparation in the form of bulk ceramics has been extensively studied. Up to now, several methods, including solid state reaction, hydrothermal synthesis, mechanical activation technique, sol-gel method, co-precipitation method were used for the preparation of bulk ceramics. Recently, the soft combustion synthesis is used as alternative route since it offers several beneficial points to the processing element and the properties of ceramics (Yan ,Razak, 2010). Bismuth titanate, Bi4Ti3O12 or BTO has received a lot of attention as dielectric and ferroelectric materials. Many studies have been conducted in various processing route to improve the microstructure that has a significance effect on dielectric and ferroelectric properties (Hardy et al., 2004, Pookmanee et al., 2004, Zhi-hui et al., 2010). In addition, a modification on basic compound is essential to enhance those properties. Since BTO is also sought as a potential material for dielectric application, in this chapter the effect of Sm3+ and Pr3+ doped-BTO was prepared and characterized by soft combustion technique. In order to investigate a possible application as wireless dielectric antenna, the dielectric study at different frequencies was carried out.